Characteristics of Grade 2 Disability in Indonesian Children with Leprosy: A Five-Year Multicenter Retrospective Study - Gunawan H; Kamilia A; Menaldi SL; Marissa M; Prakoeswa CRS; Alinda MD; Widasmara D; Basuki S; Anum Q; Ariani T; Mamuaja EH; Rusyati LMM (Dove Medical Press, 2021)
Hendra Gunawan,1- 3 Atika Kamilia,1,2 Sri Linuwih Menaldi,2- 4 Melani Marissa,2,4 Cita Rosita Sigit Prakoeswa,2,3,5 Medhi Denisa Alinda,2,5 Dhelya Widasmara,2,6 Santosa Basuki,2,6 Qaira Anum,2,7 Tutty Ariani,2,7 Enricco H Mamuaja,2,8 Luh Made Mas Rusyati2,9 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran, Hasan Sadikin Hospital, Bandung, Indonesia; 2Indonesian Leprosy Study Group - Indonesian Society of Dermatology and Venereology, Jakarta, Indonesia; 3Indonesian College of Dermatology and Venereology, Jakarta, Indonesia; 4Department of Dermatology and Venereology, Faculty of Medicine, Universitas Indonesia, Cipto Mangunkusumo Hospital, Jakarta, Indonesia; 5Department of Dermatology and Venereology, Faculty of Medicine, Universitas Airlangga, Soetomo Hospital, Surabaya, Indonesia; 6Department of Dermatology and Venereology, Faculty of Medicine, Universitas Brawijaya, Malang, Indonesia; 7Department of Dermatology and Venereology, Faculty of Medicine, Universitas Andalas, Padang, Indonesia; 8Department of Dermatology and Venereology, Faculty of Medicine, Universitas Sam Ratulangi, Prof. R. D. Kandou Hospital, Manado, Indonesia; 9Department of Dermatology and Venereology, Faculty of Medicine, Universitas Udayana, Bali, IndonesiaCorrespondence: Hendra GunawanDepartment of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, IndonesiaTel +62 812 2111 1215Email h.gunawan2016@unpad.ac.idBackground: One of the indicators of achieved leprosy control is lower new cases of leprosy with grade 2 disability (G2D), while zero new pediatric case with G2D is one of the targets of The Global Leprosy Strategy. This study aimed to describe the characteristics of leprosy in children with G2D from seven provincial hospitals in Indonesia, spanning a period of five years.Methods: This was a descriptive and retrospective study with cross-sectional design. Data were obtained from the medical records of leprosy-affected children in seven provincial hospitals in Indonesia between January 2014 and December 2019 using a total sampling method. Data obtained include characteristics of patients, clinical manifestations, and profile of leprosy in children with G2D.Results: From the 132 data of childhood leprosy retrieved, male (58.33%), age group of 13- 14 years (47.73%), and borderline tuberculoid leprosy (34.09%) comprised the majority of patients. Most of the patients had anesthetic macules as the initial manifestation. The results showed 20 (15.15%) children had G2D. Hands were the most common site affected (50.00%), manifested as claw hands, contractures, atrophy of thenar and hypothenar muscles, and pseudomutilation. Foot drop was seen in five (62.50%) children, and lagophthalmos was seen in one child with leprosy.Conclusion: This study shows that G2D is observed in 15.15% Indonesian children with leprosy at the time of diagnosis, which mostly occurs on the hands in the form of claw hands. Foot disabilities were also observed, most commonly as foot drop, while lagophthalmos was present with disabilities in the eyes. Disability due to leprosy in children really exists. The commitment of all health care services and related institutions is needed in order to reduce the incidence of disability due to leprosy in children.Keywords: children, grade 2 disability, leprosy